Preparation and optimization of chitosan nanoparticles from discarded squilla (Carinosquilla multicarinata) shells for the delivery of anti-inflammatory drug: Diclofenac. (1st December 2020) - Balde, Akshad; Hasan, Abshar; Joshi, Ila; Nazeer, R.A.
ABSTRACT: Biological waste from marine sources is discarded into various water bodies which leads to dramatic increase in the water pollution near coastal areas. This animal waste consists of bioactive compounds such as fatty acids, amino acids, and chitin which can be used in agricultural and pharmaceutical sectors. The aim of the current study was to extract chitosan (CS) from the discarded shells of Carinosquilla multicarinata and prepare anti–inflammatory drug diclofenac potassium (DP) encapsulated chitosan nanoparticles (DP-CSNPs). The CS was extracted, purified and physicochemical and morphological properties were characterized such as viscosity (1.44cPs), molecular weight ( 57 kDa), degree of deacetylation (83%). The DP-CSNPs were prepared by ionic gelation of extracted chitosan with tripolyphosphate (TPP) anions by varying chitosan, TPP, and drug concentrations. SEM imaging showed that DP-CSNPs were nano-sized (248 nm) along with small, spherical, and uniformity in shape. The endothermic peak appeared at 180°C while performing the thermal analysis of DP-CSNPs by differential scanning calorimetry (DSC). The Loading capacity (LC) and encapsulation efficiency (EE) were determined for all combinations while maximum EE (79.42%), LC (42.08%), and +0.00459 mV for Zeta potential were found for nanoparticles synthesized from CS with 2.5mg/mL concentration and 1mg/mL of TPP and drug concentrations. Moreover, in vitro drug release study was performed at simulated biological fluid (pH 7.4) and at 10th hr maximum (80%) of the drug was released from DP-CSNPs. Therefore, this waste source would be a better model system for the drug release. Implications : Dumping of marine waste into deep ocean has led to dramatic increase in water pollution leading to the endangerment of various oceanic animals. This discarded waste can be used sustainably for the isolation of various biopolymers into the ultimate use for human community. The work provides a detailed guide into the method of extraction of low molecular weight chitosan and preparation of nanoparticles for the delivery of anti-inflammatory drug diclofenac.